2004
DOI: 10.1111/j.1523-1755.2004.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite-mediated oxidative stress in kidney cells

Abstract: Micromolar sulfite elicited an immediate increase in ROS in MDCK, type II, and OK cells. This was accompanied by a depletion of intracellular ATP, which could be explained by its inhibitory effect on mitochondrial GDH. Although MDH was similarly inhibited, the impact was buffered by the high level of this enzyme in kidney mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 50 publications
4
32
0
Order By: Relevance
“…2). Similar observations have been reported with rat kidney mitochondria and MDCKII and OK cells (30). However, when other respiratory substrates, namely ␣-ketoglutarate, malate, and succinate, were added at concentrations that mimic their relative concentrations in the whole rat/mouse brain, the inhibitory effect of sulfite on ATP production was not shown (Table III).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…2). Similar observations have been reported with rat kidney mitochondria and MDCKII and OK cells (30). However, when other respiratory substrates, namely ␣-ketoglutarate, malate, and succinate, were added at concentrations that mimic their relative concentrations in the whole rat/mouse brain, the inhibitory effect of sulfite on ATP production was not shown (Table III).…”
Section: Discussionsupporting
confidence: 61%
“…The measurement of intracellular ATP was based on the luciferin-luciferase reaction. Both methods have been reported in our previous study (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In neurons and human fetal liver cells, it has also been shown that ATP is depleted due to sulfite toxicity [9]. Similar observations were made in rat kidney mitochondria and other nonneuronal cells [85]. In addition, it has been shown that sulfite inhibits mitochondrial glutamate dehydrogenase activity [9].…”
Section: Discussionsupporting
confidence: 61%
“…17 The buffer used consisted of 100 mmol/L KCl, 12.5 mmol/L KH 2 PO 4 , and 10 mmol/L Tris, pH 7.6. A total of 0.03 mg cortical mitochondria (nϭ6) was incubated with 1 mL of buffer and 125 mol/L adenosine diphosphate, complex II substrate 10 mmol/L succinate, complex I inhibitor 5 mol/L rotenone, and the presence or absence of studied drugs with or without H 2 O 2 under condition of continual shaking for 5 minutes at 24°C.…”
Section: Atp Biosynthesis In Isolated Mitochondriamentioning
confidence: 99%